The influence of islamic religious education teachers on the learning achievement of smk 2 limboto students - Maghfira Aulia Zainuddin; Adittia Batalipu (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
This study aims to identify the influence of Islamic religious education teachers on student learning achievement at SMK 2 Limboto. The research method used is quantitative method with data collection through questionnaires distributed to students in class. Data were analyzed using descriptive statistical tests, validity, reliability, normality, linearity, simple linear regression, and hypothesis testing. The linearity test showed that there was no linear relationship due to external variable factors. The results showed that there is a significant relationship between Islamic religious education teachers and student learning achievement. The regression test produces a significance value of 0.000 below 5% or 0.05, indicating that Islamic religious education teachers make a real contribution to learning achievement. The coefficient of determination of 38% shows that the religious education teacher variable affects student learning achievement, while the rest is influenced by other factors. This research confirms the importance of Islamic religious education teachers as the main factor in improving student learning achievement, which can be supported through various internal and external factors.